Students’ Understanding of Interest in Learning Science - Liou Ho; Ismawan Prasetia Devi (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: Describe the trend of shifting student interest in learning science in middle school. Methodology: This study uses descriptive qualitative and descriptive inquiry approaches in analyzing new trends of student interest in learning science in middle school. Main Findings: The findings can be concluded that the shift in interest is influenced by technology. Applications of this study: The results of this study will be useful for the pedagogical realm of teachers in teaching science. Novelty/Originality of this study: The novelty of this research interest in learning science has changed dramatically with the ease of internet access